2010
DOI: 10.1253/circj.cj-10-0820
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Risk of Atrial Fibrillation - Epidemiologic and Clinical Evidence -

Abstract: Dietary factors might affect the risk of atrial fibrillation (AF), but available studies have provided inconsistent results. A review of published observational studies and randomized trials identified 4 dietary exposures that had been investigated regarding AF risk: alcohol, fish-derived n-3 polyunsaturated fatty acids, caffeine, and ascorbic acid. Though studies were highly heterogeneous in their design and results, they showed a consistently increased risk of AF in heavy alcohol drinkers, but no risk associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 63 publications
1
13
0
1
Order By: Relevance
“…We did not separately assess risk of AF according to physical activity intensity, and these differences can not be excluded in this cohort as well. Similar to our study, prior literature has not demonstrated a reliable association between either total cholesterol or dietary components and AF 36, 37, 38, 39, 40, 41, 42. No previous studies have explored whether specific dietary patterns might be associated with the risk of AF.…”
Section: Discussionsupporting
confidence: 86%
“…We did not separately assess risk of AF according to physical activity intensity, and these differences can not be excluded in this cohort as well. Similar to our study, prior literature has not demonstrated a reliable association between either total cholesterol or dietary components and AF 36, 37, 38, 39, 40, 41, 42. No previous studies have explored whether specific dietary patterns might be associated with the risk of AF.…”
Section: Discussionsupporting
confidence: 86%
“…In most studies, we estimated caffeine exposure by coffee consumption which can lead to exposure misclassification bias. This would be expected to bias results towards the null (no association) [34]. Besides caffeine, coffee has other substances such as hypercholesterolemic compounds (cafestol and kahweol) [35], chlorogenic acid, flavonoids, melanoidins, compounds with antioxidant properties [36,37], and various lipid-soluble compounds such as furans, pyrroles, and maltol that may have either beneficial or harmful effect on the cardiovascular system [38].…”
Section: Limitationsmentioning
confidence: 99%
“…83 There have been contrasting findings on the protective effect of specific kinds of fish on AF prevention. 84,85 Long-term, highly accurate monitoring of nutritional intake, or development of nutritional biomarkers, is essential for clarifying dietary contributions to AF risk.…”
Section: Epidemiologymentioning
confidence: 99%